Sandra Helps You Learn: The More You Walk, The More Battery Your Phone Drains - MIN, Chulhong (Institutional Knowledge at Singapore Management University, 2015)
Emerging continuous sensing apps introduce new major factors governing phones’ overall battery consumption behaviors: (1) added nontrivial persistent battery drain, and more importantly (2) different battery drain rate depending on the user’s different mobility condition. In this paper, we address the new battery impacting factors significant enough to outdate users’ existing battery model in real life. We explore an initial approach to help users understand the cause and effect between their physical activity and phones’ battery life. To this end, we present Sandra, a novel mobility-aware smartphone battery information advisor, and study its potential to help users redevelop their battery model. We perform an extensive explorative study and deployment for 30 days with 24 users. Our findings reveal what they essentially learned, and in which situations they found Sandra very helpful. We share the lessons learned to help in the design of future mobility-aware battery advisors.